Benefits of Implementing or Aligning an Organization to ISO 55001 Asset Management Systems - Phillipos, George (Curtin University, 2024)
Large organizations like airlines, ports, railways and mining companies own assets that cost billions of dollars. These organizations spend several billions of dollars each year on Asset Management. Asset Management can be described to be the coordinated activities of an organization to realize value from assets. Asset Management includes, but is not limited to, procurement, preventive and corrective maintenance, asset reliability calculation and improvement, asset performance measurement, risk management, planning, competence management, leadership, audits, allocation of resources and the use of Enterprise Resource Planning (ERP) applications like SAP, Oracle and IBM Maximo to manage all of the above.